The Role of Social Investment in Human Capital Development - Losieva, Yuliia (Theory and Practice of Public Administration, 2023)
The role of social investments in the development of human capital in Ukraine has been studied. The social and economic reality of the category of human capital, its main warehouses, the significance of human capital for the economy, as well as the problems of its development in Ukraine are examined. The main problems of state-owned investment policy in direct investment of human capital are highlighted. Ways have been identified that can become a victorious power for the implementation of state policy to promote social investment in human capital. The role of social investments in the formation of human capital is analyzed. The main elements of human capital have been seen. The names of the benefits of investing in human capital for the practitioner, the pioneer of that power. The dotality of social investment in human capital and its significance for the development of welfare has been outlined.